Edukasi Upaya Mencegah Kejadian Nyeri Neuropati Diabetik Pada Pasien Diabetes Mellitus Tipe 2 Dengan Indek Glikemik Yang Tinggi di RS Bhayangkara PUSDIK Brimob Watukosek - I Made Subhawa Harsa; Andiani Andiani; Harsono Wiradinata; Andra Agnez Al Aska; Ni Putu Chintya Eka Shanty (Indonesian Journal Publisher, 2024)
Diabetes mellitus is one of the health problems that has so far been quite high and is predicted to continue to experience increases in both morbidity and mortality rates. High glycemic index in patients with type 2 diabetes treated at Bhayangkara Pusdik Brimob Watukosek Hospital is known to be a major factor in the emergence of complications of Diabetic Neuropathy Pain (NND). The purpose of this activity is to educate on the efforts to prevent the occurrence of diabetic neuropathic pain in patients with type 2 diabetes mellitus with a high glycemic index at Bhayangkara Pusdik Brimob Watukosek Hospital. The method used is carried out in three stages: planning, implementation, evaluation, and follow-up. The results of this test show an increase in public knowledge and understanding related to efforts to prevent the occurrence of diabetic neuropathy pain in patients with type 2 diabetes mellitus with high glycemic index at Bhayangkara Pusdik Brimob Watukosek Hospital based on pre-test and post-test results. The results of this activity showed that the average pre- and post-test scores increased significantly before and after education, which is 0.91 (91%).